Sensitizing the insensitive. - Ashrafian, H; Bogle, R (2004)
Lithium is still the treatment of choice in bipolar affective disorder. The patient presented here represents an example of the possible severity of metabolic defects resulting from lithium use. In this case, it caused severe intractable nephrogenic diabetes insipidus (NDI). Our case report draws attention to 2 important messages. The first is the complexity in treating psychiatric patients that is often not borne out in the medical literature. The second is the role and power of pharmacological augmentation. While the role of these agents has been appreciated for some time, the use of carbamazepine and of drug combinations is not as well recognized. We emphasize the clinical features of NDI, lithium's metabolic sequelae and furthermore collate the most up-to-date account of the signalling effects conferred by these agents in a summary diagram.